Applied economics and the critical realist critique - Downward, Paul, 1964- (London ; New York : Routledge, 2003)
This volume provides a real attempt to bridge the gap between mainstream applied economics and its critics. With refreshing open-mindedness, the contributors do not simply limit themselves to theoretical discussions, but in fact examine issues such as employment and unemployment, critical realism and econometrics and the political economy of monetary union. This book will greatly interest students and academics involved in economic methodology, philosophy and indeed mainstream economics.
Includes bibliographical references and index.
rpm 23/10/13
Loans
Keywords: Economics -- Methodology; Economics -- Philosophy; Economics -- Sociological aspects; Economics -- Econometric models; Critical realism